A Multi-Layer Architecture for Progressive Privacy Risk Mitigation in AI Applications - Lima, Leonardo Bruscagini de; Rocha, Luca Misi; Silva, Javier Martinez; Braga, Alexandre Melo (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2026: Anais Estendidos do XXVI Simpósio Brasileiro de CibersegurançaDO - 10.5753/sbseg_estendido.2026.28883, 2026)
AI applications process sensitive data and remain exposed to inference and reconstruction attacks. Privacy-Enhancing Technologies (PETs) are often deployed in isolation, allowing risks to accumulate across AI pipelines. This paper presents a Multi-Layer Architecture for Progressive Privacy Risk Mitigation that integrates semantic PII sanitization, structured anonymization, Differential Privacy, adversarial validation, and governance auditing. Experiments with Microsoft Presidio, ARX/PyCANON, and Opacus are combined with a reproducible pipeline that preserves layer interfaces and privacy metrics. Results show improved PT-BR PII detection, utility-aware anonymization, and lower inference and reconstruction exposure.